Beneficial Plant-Associated Microorganisms From Semiarid Regions and Seasonally Dry Environments: A Review - Bonatelli, Maria Leticia; Lacerda-Júnior, Gileno Vieira; dos Reis Junior, Fábio Bueno; Fernandes-Júnior, Paulo Ivan; Melo, Itamar Soares; Quecine, Maria Carolina (Frontiers in Microbiology, 2021)
Semiarid regions are apparently low biodiversity environments; however, these environments may host a phylogenetically diverse microbial community associated with plants. Their microbial inhabitants are often recruited to withstand stressful settings and improve plant growth under harsh conditions. Thus, plant-associated microorganisms isolated from semiarid and seasonally dry environments will be detailed in the present review, focusing on plant growth promotion potential and the microbial ability to alleviate plant abiotic stress. Initially, we explored the role of microbes from dry environments around the world, and then, we focused on seasonally dry Brazilian biomes, the Caatinga and the Cerrado. Cultivable bacteria from semiarid and seasonally dry environments have demonstrated great plant growth promotion traits such as plant hormone production, mobilization of insoluble nutrients, and mechanisms related to plant abiotic stress alleviation. Several of these isolates were able to improve plant growth under stressful conditions commonly present in typical semiarid regions, such as high salinity and drought. Additionally, we highlight the potential of plants highly adapted to seasonal climates from the Caatinga and Cerrado biomes as a suitable pool of microbial inoculants to maintain plant growth under abiotic stress conditions. In general, we point out the potential for the exploitation of new microbial inoculants from plants growing in dry environments to ensure a sustainable increase in agricultural productivity in a future climate change scenario.